DEVELOPING INTERCULTURAL AWARENESS IN ENGLISH LANGUAGE TEACHING - Hamida Salimova Isomiddin kizi; Ruzmetova Diana Komilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The quantitative results show that although lecturers are aware of the importance of integrating both home and target culture into the classes, and developing learners‘ interactional skills, intercultural communicative competence and intercultural sensitivity, they are not sure about how to put intercultural learning into practice for EFL classroom tasks and activities. Accordingly, the results of the interview present the problems that prevent teaching about intercultural awareness and reveal that lecturers need guidance and training to practice confidently intercultural competence teaching in the classroom, especially in terms of assessment methods as they do not have a clear idea about the assessment and evaluation methods to apply with intercultural competence.